(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Obtaining a clear graft after repeat keratoplasty is still a challenging task for corneal transplant surgeons. Corneal transplant rejection rate is significantly increased in repeat keratoplasty compared with first keratoplasty. Activation of nuclear factor kappa B (NF-kB) plays a key role in the pathogenesis of rejection of transplants of various organs and tissues, primarily due to production of proinflammatory cytokines (TNF, IL-1, etc.). Purpose: To assess the role of transcription factor NF-kB in lymphocyte subsets in the prognosis of outcomes for patients undergoing repeat keratoplasty. Material and Methods: Forty-six patients (46 eyes) who underwent repeat keratoplasty were included. Of these, 30 patients (group 1) developed an opacified graft, and 16 (group 2) obtained a clear graft. Patient age ranged from 32 to 88 years. Imaging flow cytometry (ImageStream Mark II – AMNIS) and Amnis NF-kB Translocation Kits (ACS10000, Millipore, Sigma) were used to assess percentages of the cells with translocation of the NF-kB p65 subunit for lymphocyte subsets. Statistical analyses were conducted using Statistica 13.0 (StatSoft, Tulsa, OK, USA) software. The Mann–Whitney test was used to assess significance of differences. Results: Percentages of the cells with translocation of the NF-kB p65 subunit were higher in group 1 compared with group 2, particularly, for T-helpers (26.5[17; 29] vs 12.2[11;21]; p=0.003), cytotoxic T-cells (24.0[17;28] vs 11.5[7;15]; p=0.006), NK cells (45.0[34;53] vs 18.2[16;39]; p=0.014), Th17 cells (23.9[18;31] vs 14.3[12;21]; p=0.002), regulatory T cells (30.4[21;34] vs 17.4[16;22]; p=0.001) and activated T helpers (21.918;28] vs 11.4[11;17]; p=0.002). Conclusion: There were substantially increased percentages of activated cells in lymphocyte subsets (with the most pronounced increase for NK cells) of patients who developed an opacified graft compared to those who obtained a clear graft following re-keratoplasty. Assessment of percentages of the cells with translocation of the NF-kB p65 subunit for lymphocyte subsets provides valuable information for predicting graft rejection following re-keratoplasty.